1980
DOI: 10.1080/0097840x.1980.9936094
|View full text |Cite
|
Sign up to set email alerts
|

Life Events as Predictors of Academic Performance

Abstract: As part of a larger study, information was obtained about the life events which had occurred in the one-and-ten-year periods prior to entrance into a study of 169 students at a large midwestern university. Different methods of calculating life change were utilized, and these measures were correlated with the students' subsequent grade point averages over the next three years. Results demonstrated a significant negative association between life change and academic performance for the first-and second-but not fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…For minority athletes, although the psychosocial variables of life stress and competitive trait anxiety were ACT Credit Hours unrelated to academic performance, the academic variables, specifically ACT, did predict semester GPA. In terms of the psychosocial variables, these findings differ from previous studies that have found inverse life stress-academic performance relationships (De Meuse, 1985;Garrity & Ries, 1985;Lloyd et al, 1980). This inconsistency in results may be due to demographic differences; that is, the participants in previous investigations were predominantly nonminority and represented male and female nonathlete undergraduates.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…For minority athletes, although the psychosocial variables of life stress and competitive trait anxiety were ACT Credit Hours unrelated to academic performance, the academic variables, specifically ACT, did predict semester GPA. In terms of the psychosocial variables, these findings differ from previous studies that have found inverse life stress-academic performance relationships (De Meuse, 1985;Garrity & Ries, 1985;Lloyd et al, 1980). This inconsistency in results may be due to demographic differences; that is, the participants in previous investigations were predominantly nonminority and represented male and female nonathlete undergraduates.…”
Section: Discussioncontrasting
confidence: 96%
“…Other studies (e.g., De Meuse, 1985;Garrity & Ries, 1985;Lloyd, Alexander, Rice, & Greenfield, 1980) attempting to explain the academic performances of college students have focused on the effects of a psychosocial variable, life events stress, which has been defined as individuals' psychological reactions and adaptations to the occurrence of major life events (e.g., marriage, death of a close friend). For example, Lloyd et al (1980) reported significant negative relationships between life stress and GPAs taken at subsequent 1-and 2year intervals. No relationship between life stress and GPA were found for the third year after the stressor.…”
mentioning
confidence: 99%
“…Consistent with previous research, high scorers on either or both scales were expected to describe themselves as more distressed than low scorers oft self-report measure. An association between high stressful life events and poorer academic performance was predicted, as has been described in previous studies (15).…”
Section: Introductionmentioning
confidence: 62%
“…Application ofstress management in ASIP. Stress has been found to be associated with negative academic outcomes (DeMeuse, 1985;Garrity & Reis, 1985;Lloyd, Alexander, Rice, & Greenfield, 1985). For example, Lloydetal.…”
Section: Student Programmingmentioning
confidence: 99%